Pentingnya Komunikasi Keluarga Yang Baik Terhadap Kesejahteraan Lanjut Usia (Lansia) - Narma Simbolon; Gusti Pirandy (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Communication is an interpersonal process that involves verbal and non-verbal changes. Communication refers not only to the content but also to the feelings and emotions in which the individual conveys the relationship, because of that communication must be done as selectively as possible, the elderly for example, need to require special attention from everyone. Seniors in the family play the role of parents, as well as grandparents. Status and other related roles of individuals in a family will change through various ways that take place in the family life cycle. Elderly is a vulnerable age group and needs special attention from the family. Elderly social welfare is an action as an effort to meet the needs of the community, especially the elderly who cannot carry out their social functions, namely by providing assistance and support services. As a result of physical, psychological, emotional and social changes, the elderly demand good communication patterns. This study uses the evaluation method, the results of the study indicate that the importance of good family communication for the social welfare of the elderly. The results of this study can be used as additional knowledge, in providing counseling to families about the importance of implementing good communication in the elderly, and can provide treatment for family problems in elderly care.